KEPEMIMPINAN KREATIF DI SEKOLAH (SEBUAH KONSEP UNTUK MENINGKATKAN KARAKTER SISWA) - Zahro, Siti Amanatul; Syaifulloh, Ahmad (STKIP Pesisir Selatan, 2026)
Modern education faces great challenges due to technological developments, changing patterns of social interaction, and the swift flow of information that affects the formation of student character. Schools are no longer a space for knowledge transfer, but as a center for moral development that requires innovative leadership to answer the demands of the times. Departing from these issues, this study aims to describe the concept of creative leadership as a strategic approach in improving student character. This research uses a qualitative method with a literature study design, which examines books, journal articles and various relevant scientific sources regarding creative leadership and character education. The analysis was done descriptively through the process of data reduction, presentation of findings, and drawing interpretative conclusions. The results of this study show that creative leadership has a strategic role in shaping student character through the creation of an innovative, collaborative and adaptive learning environment to technological developments. Creative leaders are able to design interactive learning programs, provide experimental space for teachers and students and foster a positive school culture. Creative leaders are able to design policies that are responsive to the needs of the times, strengthen digital literacy, utilize technology as a learning tool.